Pengaruh Orang Tua Terhadap Karakter Disiplin Dalam Belajar Siswa Kelas Tinggi SDN Tanjung Selamat Aceh besar - Khalisah Khalisah; Alfiati Syafrina; Sulaiman Sulaiman (Universitas Syiah Kuala, 2023)
The aim of the study was to describe the influence of parents on the character discipline in study students at higher grades in SDN Tanjung Selamat. The approach in research is uses a quantitative approach with the type of correlational research method. This research was held in SDN Tanjung Selamat Aceh Besar with a total sample of 46 students participating consisting of all students from grades IV to VI. Data collection techniques in this study used a questionnaire using a Likert scale. In the data analysis technique used the Product Moment correlation test formula and hypothesis testing is calculated using the t test formula with a significance level of 5% (0.05). The result obtained from this study is that parents' and students' discipline in learning have a correlation value of (0.584) which is included in the medium category. Parents have an influence of 34.1% on discipline in student learning. The results of hypothesis testing obtained t-count of 4.772, this indicates that t-count (4.772) t-table (2.021) therefore it is concluded that Ho is rejected and Ha is accepted. The conclusion of this study was obtained is a significant influence of parents on the character of discipline in study students at higher grade in SDN Tanjung Selamat Aceh Besar.